The Public Value of the Humanities - Bate, Jonathan (The WISH List, 2011)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. Recession is a time for asking fundamental questions about value. At a time when governments are being forced to make swingeing savings in public expenditure, why should they continue to invest public money funding research into ancient Greek tragedy, literary value, philosophical conundrums or the aesthetics of design? Does such research deliver 'value for money' and 'public benefit'? Such questions have become especially pertinent in the UK in recent years, in the context of the drive by government to instrumentalize research across the disciplines and the prominence of discussions about 'economic impact' and 'knowledge transfer'. In this book a group of distinguished humanities researchers, all working in Britain, but publishing research of international importance, reflect on the public value of their discipline, using particular research projects as case-studies. Their essays are passionate, sometimes polemical, often witty and consistently thought-provoking, covering a range of humanities disciplines from theology to architecture and from media studies to anthropology.